Inovasi ekonomi syariah berbasis digital: Studi kasus penerapan QRIS dan Mobile banking pada BSI KCP Pekalongan - Nur Istiqomah; Tamamudin Tamamudin; Ayatullah Sadali (Journal of Accounting and Digital Finance, 2025)
The advancement of digital technology has encouraged Islamic financial institutions to innovate in delivering services to the public. One of the innovations implemented is the use of Quick Response Code Indonesian Standard (QRIS) and mobile banking as financial transaction tools that are fast, secure, and compliant with Islamic principles. This study aims to analyze the implementation of QRIS and mobile banking at Bank Syariah Indonesia (BSI) KCP Pekalongan and their contribution to supporting digital-based Islamic economic innovation. This research employs a descriptive qualitative approach using a case study method. Data collection techniques include observation, in-depth interviews, and documentation involving customers and bank staff. The results show that the application of QRIS and mobile banking facilitates customer transactions, accelerates service delivery, and enhances efficiency and transparency in financial processes. These digital innovations also promote Islamic financial inclusion, particularly among micro, small, and medium enterprises (MSMEs) and the younger generation. However, challenges remain, such as low digital literacy and limited network access in some areas. Therefore, continuous education and outreach strategies are essential to maximize the benefits of digital Islamic financial services across all segments of society.